Competitive relationship birds of Antarctica in the local focus of human activity (the example UAS "Akademik Vernadsky") - V.M. Smagol; O.O. Salgansky (Ukrainian Antarctic Journal, 2015)
The example of interspecies relationship birds-euryphages Aпtarctic species displayed competition in artificial trophic localities - in the hearth of recycling kitchen waste. ln particular, Kelp Gull (Larus dominicanus), South Polar Skua (Catharacta maccormicki), Pale-faced Sheathbill (Chionis alba) and Southern Giant Petrel (Macronectes giganteus) form а commensal relationship with the employees of the station (useful for birds and indifferent for men). At the same time, between themselves they show the hard rivalry of the trophic resources. Seagulls are the main species of avifauna, which for the year is changing its competitors. From November to April skuas are competitors for the gulls. They have а superiority in the number for February and March. Since the second half of April gulls compete with sheathbills. The gradual disappearance of sheathbills observed in winter - as а consequence of the appearance and aggression of skuas. ln summer, near the station occasionally observed petrels, which in spite of а small synanthropes, monopolize feed.